Trade in Services Negotiations : A Guide for Developing Countries - Sáez, Sebastián (World Bank, 2012)
The aim of this book is to help policy makers, especially in the least developed countries, address the complexities of the organization, formulation, and implementation of trade-related reforms in the service sector. The book provides a conceptual framework for trade policy making and negotiation and practical tools that may be used to guide negotiations on policies that affect the trade and investment in services. The aim is not to be prescriptive, but to provide practical recommendations and tools that may be applied in the pursuit of negotiations on services, including consultations and regulatory audits. Negotiators often have little basic information regarding existing regulations and the purpose of these regulations. This problem is compounded by the difficulty of translating existing regulations into the terminology and concepts used in trade agreements. Different methodological approaches are needed to manage different sets of laws and regulations. This book offers a simple tool to help countries organize information to address these challenges. The book also provides practical examples and negotiation exercises that aim to enhance understanding of ways to use the conceptual framework and related tools.